2006
DOI: 10.1088/0960-1317/16/10/022
|View full text |Cite
|
Sign up to set email alerts
|

Application of capillary forces and stiction for lateral displacement, alignment, suspension and locking of self-assembled microcantilevers

Abstract: We report the surface-tension-powered self-assembly (displacement, alignment, pulling down and locking) of microcantilevers. Capillary forces-assisted displacement is realized by compression of four arrays of springs linked to the opposite lateral sides of the cantilevers. After in-plane translation along the initial cantilever orientation, the microstructure is pulled down and locked on the substrate by stiction. Spring and capillary forces are described with a simple analytical model. Complete self-assembly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…This can lead to partial self-alignment (A 1 ), corner self-alignment (A 2 ) or edge self-alignment (A 3 ). 70,71 The component may conversely overshoot past the receptor edge and pull the contact line with it, away from the edge, when small liquid viscosity and/or large liquid volumes induce underdamped motion. Insufficiently large offsets may also not be conducive to the alignment conditions A 1 -A 3 .…”
Section: Shape Matchingmentioning
confidence: 99%
See 1 more Smart Citation
“…This can lead to partial self-alignment (A 1 ), corner self-alignment (A 2 ) or edge self-alignment (A 3 ). 70,71 The component may conversely overshoot past the receptor edge and pull the contact line with it, away from the edge, when small liquid viscosity and/or large liquid volumes induce underdamped motion. Insufficiently large offsets may also not be conducive to the alignment conditions A 1 -A 3 .…”
Section: Shape Matchingmentioning
confidence: 99%
“…73 The capillary force of molten solder bumps between matching pads on both board and sensors was exploited, and three devices were assembled simultaneously. A capillary approach was also applied to the fluidic assembly of a GaAs-based microcantilever spin injector, 70 microcantilever for atomic force microscopy, 71 and of millimeter-sized components with inner cavities. 63 In this case the hydrophilic receptors, coated with a thin layer of water-diluted hydrofluoric acid, matched only the perimeter of the components.…”
Section: Shape Matchingmentioning
confidence: 99%
“…Agache et al investigated stiction-controlled locking systems for 3D microstructures such as scratch drive actuators [16]. Rose et al reported on the application of stiction and capillary forces to the precise lateral displacement, alignment, suspension and locking of microcantilevers for atomic force microscopy applications [17]. …”
Section: Self-assembly Of Microelectromechanical Structuresmentioning
confidence: 99%
“…A nice combination of stiction and surface tension is described in [134]. A spring is contacted by the drying liquid, moving a construction laterally on the wafer (in this case a cantilever beam with an atomic force microscope tip).…”
Section: Self-assembly In Memsmentioning
confidence: 99%